Toward Green Liquid Nitrogen Fertilizer Synthesis: Plasma‐Driven Nitrogen Oxidation and Partial Electrocatalytic Reduction - Zhongping Qu; Jungmi Hong; Yuting Gao; Jing Sun; Jingwen Huang; Mingyan Zhang; Mengying Zhu; Tianyu Li; Xiangyu Wang; Dingwei Gan; Qiang Song; Tianqi Zhang; et al. (Advanced Science)
Abstract Liquid fertilizers, particularly when integrated with precision irrigation systems, offer a more efficient and sustainable alternative to traditional solid nitrogen fertilizers. The industrial production of ammonium nitrate (NH4NO3) is environmentally detrimental due to its reliance on fossil fuels. This study introduces an innovative air‐to‐NOx‐to‐NH4NO3 pathway for synthesizing liquid nitrogen fertilizer. The process employs an underwater multi‐bubble plasma reactor powered by nanosecond pulse to generate aqueous NOx, which is then partially reduced to NH4NO3 through electrocatalysis. Results show that the highest NOx production rate, 786.5 mol h−1, is achieved when the N2/O2 ratio closely resemble that of air, and short pulse rise/fall times significantly increase NOx yield. Further plasma diagnostic and global plasma chemistry modeling indicate that short rise/fall times facilitate simultaneous dielectric barrier discharge and spark discharge, synergistically enhancing nitrogen fixation efficiency. The partially electro‐reduced liquid NH4NO3 fertilizer significantly improves plant growth, with stem length and leaf length increasing by 91.26% and 54.72%, respectively. Cost estimation reveals that 44.22% of the production cost is attributed to electricity consumption, underscoring the potential for optimization with renewable energy integration. Overall, the study provides new insight for the sustainable production and in‐place utilization of liquid nitrogen fertilizers which may advance sustainable agriculture.